2013
DOI: 10.1002/xrs.2526
|View full text |Cite
|
Sign up to set email alerts
|

X-ray quasi-lamellar etched multilayers: analysis by coupled-mode theory

Abstract: An etched multilayer (EM) is a two-dimensional structure obtained by etching a periodic multilayer following the profile of a grating. Generally a laminar grating shape, i.e. with a rectangular shape, is desired. However, we observe that different EM give different diffraction efficiency curves. We implement the coupled-mode theory to calculate the diffraction pattern of the EM as a function of the shape of the etching profile. Thus, we try to correlate the variability of the experimental reflectivity curves t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Recently, the coupled-mode theory was implemented to calculate the diffraction pattern of the EM as a function of the shape (rectangular or trapezoidal) of the etching profile for different values of Γ [20]: these calculations show that (i) the secondary peaks observed in Figure 4 originate from the coupling of the 1st order of diffraction by the multilayer with the orders of diffraction by the grating (ii) the relative intensity of the secondary peaks depends on the shape of the lines of the grating. The limited gain in bandwidth (∼1.5) in the B K region can be improved by diminishing the period D of the grating (the grating diffraction orders would then be better separated from the 1st multilayer diffraction order [21]) and by a better control of the rectangular patterning of the grating lines.…”
Section: -P3mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the coupled-mode theory was implemented to calculate the diffraction pattern of the EM as a function of the shape (rectangular or trapezoidal) of the etching profile for different values of Γ [20]: these calculations show that (i) the secondary peaks observed in Figure 4 originate from the coupling of the 1st order of diffraction by the multilayer with the orders of diffraction by the grating (ii) the relative intensity of the secondary peaks depends on the shape of the lines of the grating. The limited gain in bandwidth (∼1.5) in the B K region can be improved by diminishing the period D of the grating (the grating diffraction orders would then be better separated from the 1st multilayer diffraction order [21]) and by a better control of the rectangular patterning of the grating lines.…”
Section: -P3mentioning
confidence: 99%
“…3.2) has shown that unfortunately, although optimized for the B K domain, the structure does not allow a significant reduction of the width of the Bragg peak in that region due to the coupling of the 1st order of diffraction by the multilayer with the orders of diffraction by the grating [20]. On the other hand, in the C K range, despite a low reflectance (0.65 %), the gain in spectral resolution is valuable.…”
Section: Insertion In a High-resolution Curved-crystal Johann-type Spmentioning
confidence: 99%